Comparative analysis of stromal inflammatory cell infiltration and HPV infection status in cervical dysplasia and squamous cell carcinoma using the Klintrup-Mäkinen Scoring method - Nicholas Adrian Fahendra; Daniel Edbert; Christian Ardianto; Lilis Lilis (Majalah Obstetri & Ginekologi, 2025)
HIGHLIGHTS KM score is a reliable method to help determine the diagnosis of cervical dysplasia and squamous cell carcinoma. KM score cannot be used to differentiate infection status in cervical dysplasia and squamous cell carcinoma.   ABSTRACT Objective: Cervical cancer is the second most common malignancy in women, with 604,127 new cases reported globally in 2020. Persistent high-risk human papillomavirus (HPV) infection is the primary cause. This study aimed to evaluate the relationship between stromal inflammatory cell infiltration using the Klintrup-Mäkinen (KM) score and HPV infection status in cervical dysplasia and squamous cell carcinoma (SCC). Materials and Methods: A cross-sectional study was conducted using secondary data from formalin-fixed paraffin-embedded (FFPE) cervical tissue samples diagnosed as dysplasia or SCC at Atma Jaya Catholic University of Indonesia from 2014 to 2022. HPV status was determined using PCR-based assays, while stromal inflammatory cell infiltration was assessed microscopically at 100× magnification and graded according to the KM scoring system by two blinded observers. Statistical analyses, including Chi-square and Spearman’s correlation tests, were performed using STATA/IC 15, with p < 0.05 considered significant. Results: A total of 38 samples were analyzed, comprising 20 (52.63%) cases of dysplasia and 18 (47.37%) cases of SCC. HPV positivity was identified in 70% of dysplasia and 94.44% of SCC cases. KM scores of 2/3, indicating moderate to severe inflammatory infiltration, were significantly more frequent in SCC (77.78%) compared to dysplasia (20%), showing a strong association with pathological diagnosis (p = 0.0019). However, no significant correlation was observed between KM score and HPV status in either lesion type. Conclusion: The KM scoring method provides a reliable and cost-effective approach for assessing stromal inflammatory cell infiltration in cervical lesions, aiding histopathological diagnosis, although it does not predict HPV infection status.